P148 CANCER INCIDENCE AND MORTALITY ACCORDING TO PRE–EXISTING HEART FAILURE IN A COMMUNITY–BASED COHORT. (18th May 2022) - Bertero, E; Robusto, F; Rulli, E; D'Ettore, A; Staszewsky, L; Maack, C; Lepore, V; Latini, R; Ameri, P
Abstract: Background: Studies assessing whether heart failure (HF) is associated with an excess risk of cancer and cancer–related mortality yielded conflicting results. Here, we assessed the incidence and mortality of cancer according to the presence of HF in a community–based cohort. Methods: By reviewing the health care records of the Puglia region in Italy, we first selected the individuals ≥50–year–old, with no history of cancer within 3 years before the baseline evaluation and ≥5 years of follow–up, during the period from January 1st, 2005 to December 31st, 2013. Next, we matched 1:1 104, 020 subjects with HF at baseline and 104, 020 controls based on age, sex, Drug–Derived Complexity Index, and follow–up duration. Cancer incidence and mortality were analyzed by Kaplan–Meier method and Cox regression models. Fine and Grey's regression model was also used to compare cancer–specific mortality while taking into account the competing risk of non–cancer death. Results: Overall, the mean age of the study population was 76±10 years and the mean follow–up was 5.7 years. The incidence rate of cancer in HF patients and controls was 21.36 (95%CI, 20.98–21.74) and 12.42 (95%CI, 12.14–12.72) per 1000 person/years, respectively, corresponding to a 76% higher risk of incident cancer in HF patients (HR, 1.76; 95%CI, 1.71–1.81). HF patients also died from cancer more frequently than controls (HR 4.11; 95%CI, 3.86–4.38; Figure 1 ). This excess mortality was highest when age was <70 years (HR 7.54, 95%CI 6.33–8.98), and declined in subjects aged 70–79 years (HR 3.80, 95%CI 3.44–4.19) and ≥80 years (HR 3.10, 95%CI 2.81–3.43). The association of HF with cancer mortality was confirmed in the competing risk analysis (subdistribution HR 3.48, 95%CI 3.27–3.72), as well as the interaction with age: <70 years of age: SHR 6.65, 95%CI 5.60–7.94; 70–80 years: SHR 3.14, 95%CI 2.84–3.48; and ≥80 years: SHR 2.81, 95%CI 2.55–3.10. The HF–related risk applied to the majority of cancer types. Interestingly, among HF patients a high consumption of loop diuretic (≥80 mg/d of furosemide equivalents for ≥30 days in the year before the index date) was associated with a higher mortality for cancer (HR 1.35, 95%CI 1.19–1.53 vs. ≤37.5 mg/d). Conclusions: The analysis of this large community–based sample suggests that HF does portend an increased risk of cancer and cancer–related mortality, which is blunted, yet remains substantial, with increasing age and competing risk of dying from other causes.